Good business exercising effective and ethical leadership - O?Toole, James (New York Routledge, 2001)
This illuminating and practical collection of essays addresses the increasingly important topics of corporate ethics, social responsibility, and sustainability in the context of effective global business strategies. Instead of condemning business, or exhorting corporate leaders to "do good," the authors deal with the "hot button" issues of our time in a cool and rational manner, seeing them as opportunities rather than as problems. As the authors illustrate, there is no necessary trade-off between business leaders doing the right thing, on one hand, and the profitable thing, on the other. They demonstrate that ethics is not peripheral, or in addition to, the central concerns of business. To the contrary, ethics and good citizenship are at the heart of all good business strategies, decisions, and organizational cultures. These essays offer useful examples of how executives can create strategies and cultures that are, both and at the same time, ethical and effective--the essence of GOOD BUSINESS.
"A publication of the Institute for Enterprise Ethics."
Keywords: Corporate culture